As árvores do cerrado sentido restrito no Clube Caça e Pesca Itororó, Uberlândia, Minas Gerais, Brasil. - Silva, Letícia Maria Souto (2020)
Clube Caça e Pesca Itororó in the municipality of Uberlândia, Minas Gerais, has an area of 127 hectares of savannah and due to its importance it was recognized as a Private Reserve of Natural Heritage (RPPN). However, the area has not been registered and the remaining cerrado is currently unprotected, leaving the associated flora and fauna vulnerable to the advance of urban growth. The club's cerrado area is divided into two main phytophysiognomies of the savanna formation: cerrado restricted sense and footpath. The restricted sense cerrado has been studied in structural terms and systematic treatments of some families of angiosperms (e.g. Melastomataceae and Asteraceae), but there is no work on the floristics of the tree species of this phytophysiognomy. Thus, the objectives of the present work are to carry out the survey of the trees that occur in the cerrado area in a restricted sense, as well as to elaborate a photographic guide of the species and to recognize the conservation status and possible endemisms. The survey was carried out through studies of specimens collected in the dry and rainy seasons, between April 2018 and March 2019, as well as the specimens deposited at the Herbarium Uberlandense (HUFU) of the Biology Institute of the Federal University of Uberlândia, Minas Gerais. The floristic survey indicates a wealth of 63 species belonging to 46 genera, distributed in 26 families. The richest families were Fabaceae (16 spp.), Vochysiaceae (six spp.) And Apocynaceae, Melastomataceae and Myrtaceae (four spp. Each). Regarding conservation status, one species is said to be almost threatened: Bowdichia virgilioides Kunth. In addition to this species, Caryocar brasiliense Cambess. (pequi) is protected from cutting by the legislation of the state of Minas Gerais. As for endemism, 13% are restricted to Brazil (eight spp.), 13% to the Cerrado biome (eight spp.) And 8% (five spp.) Concomitantly restricted to Brazil and the Cerrado biome. Due to the relevance of the Cerrado restricted area of Clube Caça e Pesca Itororó, with a floristic composition representative of the Cerrado, it is urgent that this remnant be protected again, thus guaranteeing the conservation of this important genetic heritage.